2004
DOI: 10.1007/bf02803260
|View full text |Cite
|
Sign up to set email alerts
|

Resprouting after disturbance: an experimental study with short-lived monocarpic herbs

Abstract: Abstract:We experimentally demonstrated the ability of three short-lived monocarpic species to vegetatively regenerate (resprout) from roots after severe disturbance. We assessed the relationship between resprouting ability and (1) timing of injury with respect to life-cycle stage (reproductive vs. vegetative plant), life-history mode (annual vs. winter annual) and phenological stage (flowering vs. fruiting plant), (2) nutrient availability, and (3) disturbance severity (removal of all axillary buds Yes/No).In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…Dubard (1903) and Rauh (1937) noticed that the biennials Alliaria officinalis and Bryonia dioica were able to sprout from roots only at the end of the first growing season, and the shortlived herb Oenothera biennis was only in vegetative stage (rosette). According to a more recent study (Martı´nkova´et al, 2004a), O. biennis regenerates from roots also in the generative phase (fruiting stem), but less successfully than in the vegetative stage. The same result was found for the short-lived perennial Barbarea vulgaris (Martı´nkova´et al, in prep.).…”
Section: Internal Factorsmentioning
confidence: 97%
See 3 more Smart Citations
“…Dubard (1903) and Rauh (1937) noticed that the biennials Alliaria officinalis and Bryonia dioica were able to sprout from roots only at the end of the first growing season, and the shortlived herb Oenothera biennis was only in vegetative stage (rosette). According to a more recent study (Martı´nkova´et al, 2004a), O. biennis regenerates from roots also in the generative phase (fruiting stem), but less successfully than in the vegetative stage. The same result was found for the short-lived perennial Barbarea vulgaris (Martı´nkova´et al, in prep.).…”
Section: Internal Factorsmentioning
confidence: 97%
“…Rauh (1937) found the same strategy in Geranium sanguineum and Rumex sanguineus. On the other hand, Oenothera biennis forms root buds and releases new root-borne shoots almost exclusively after injury (Martı´nkova´et al, 2004a), even though these buds are not formed directly on the callus tissue as in some other species, e.g., Trifolium alpestre, Centaurea scabiosa (Rauh, 1937).…”
Section: External Factorsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the ability of annuals to form buds de novo and regenerate vegetatively from them was not sufficiently studied to evaluate its potential role in the weediness of such species. The few experiments done so far were focused predominantly on regeneration of Rorippa palustris from root fragments (Martínková et al 2004a(Martínková et al ,b, 2006Klimešová et al 2007) or Linum usitatissimum and Euphorbia geniculata from the hypocotyl (Adams 1924;Crooks 1933;Rauh 1937;Eggers 1946;Link & Eggers 1946;Kigel et al 1992; 924 V. Latzel et al Ishikawa et al 1997). Experiments with Rorippa palustris found that plants that regenerated from root fragments can finish their life cycle and even produce more seeds than plants regenerating from seeds .…”
Section: Introductionmentioning
confidence: 99%